NITRIC OXIDE PRODUCTION AND ANTIOXIDANT ACTIVITY OF DRIED FRUIT EXTRACTS OF TERMINALIA CHEBULA - Dhanasezhian, Aridass; Srivani, Seetharaman; Rameshkumar, Marimuthu Ragavan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The dried ripe fruits of Terminalia chebula have traditionally been used to treat various ailments as it has a wide spectrum of pharmacological activities. Hence, in the present study, we aimed to explore the antioxidant activity, nitric oxide production, cytotoxicity, and phytocompounds present in the aqueous and methanol extract of T. chebula. Methods: The dry fruits of T. chebula were extracted using water and methanol, and the extracts were concentrated by lyophilization method. Phytochemical analysis was done by gas chromatography and mass spectrometry and Fourier-transform infrared spectroscopy. The free radical scavenging activity of T. chebula was estimated by 1,1diphenyl 2, picrylhydrazyl method. RAW 264.7 cells were stimulated with aqueous and methanol extracts, and the production of nitric oxide was estimated by spectrophotometric method using Griess reagent. Cytotoxicity assay was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method and percentage of cell viability was calculated. Results: Aqueous and methanolic extracts of the dry fruit of T. chebula showed non-toxic to RAW 264.7 cells at the concentration of 2 mg and 1.5 mg, respectively. These concentrations showed high free radical scavenging activity and production of optimum concentration of nitric oxide in RAW 264.7 cells. Conclusion: Fruit extracts of T. chebula possess properties of nitric oxide production and high free radical scavenging activity; these properties could be useful in the development of immunomodulatory drugs as well as protection against various human diseases associated with oxidative stress.